Digital Metasurface with Phase Code and Reflection–Transmission Amplitude Code for Flexible Full‐Space Electromagnetic Manipulations. Issue 8 (25th January 2019) - Wu, Rui Yuan; Zhang, Lei; Bao, Lei; Wu, Liang Wei; Ma, Qian; Bai, Guo Dong; Wu, Hao Tian; Cui, Tie Jun
Abstract: Digital coding metasurfaces have been introduced to describe the properties of metasurfaces digitally and provide a new approach to link the physical world and information science. However, most of the current digital metasurfaces are focused on phase code, limiting their functions and applications. Here, the concept of reflection–transmission (R–T) amplitude code is established, and novel digital metasurfaces for full‐space electromagnetic (EM) manipulations are proposed, in which the digital states of the R–T amplitude code "0" and "1" represent the total reflection and transmission, respectively. The introduction of the R–T amplitude code enables a full‐space communication system and larger information capacity by associating with phase codes. For this purpose, first a novel polarization‐dependent R–T amplitude code is proposed, which is distinguished by the polarization of the incidence. Further positive–intrinsic–negative (PIN) diodes are adopted to realize dynamic R–T amplitude code, resulting in real‐time controls of far‐field radiation characteristics. Good agreements between simulations and experiments demonstrate the powerful ability to manipulate the EM waves by combining the R–T amplitude and phase codes, indicating great potentials in new digital metasurface‐based information, radar, and imaging systems. Abstract : This article establishes the concept of reflection–transmission amplitude code for digital metasurfaces to realize more advanced simultaneous controls or real‐time controls of electromagnetic waves in full space, which can considerably improve the inherent information entropy of the digital metasurface, and has potential applications in real‐time, multitarget, and full‐space information systems.